Synthesis of Nickel Nanoparticles and Characterization by Thermal Decomposition of Ni(2,4-di-ClPhAc)2(N2H4)1.5·H2O - Sinduja, C.R.; Kalpanadevi, K.; Manimekalai, R. (Asian Journal of Chemistry, 2014)
Nickel nanoparticles have been successfully prepared from nickel carboxylate hydrazinate hydrate as a precursor followed by thermal decomposition. Ni(2,4-di-ClPhAc)2(N2H4)1.5·H2O has been prepared and characterized by hydrazine, metal analyses, electronic spectra, infrared spectra and thermal analysis. The precursor shows multistep decomposition to form metallic Ni. The structure and morphology of as prepared Ni nanoparticles were characterized by powder X-ray diffraction, scanning electron microscope, high resolution transmission electron microscope and selected area electron diffraction. The synthesized Ni nanoparticles have average particle size of about 28 nm. This simple and inexpensive synthetic procedure can also be employed to prepare other transition metal nanoparticles.